ANALISIS UNDERPRICING DI PASAR SEKUNDER BURSA EFEK INDONESIA - Putri Noviyana, (2013)
This study aims to test whether the variables Age Company, Market Return (market conditions) and company size significantly influence Underpricing in companies listed on the Stock Exchange 2010-2012. The population was 70 whole company doing an IPO (Initial Public Offering) in 2010-2012. Data obtained from the published financial statements of the company. With a total sample of 36 companies. The analysis technique used is multiple linear regression and hypothesis testing using the F test and t test with a confidence level of 5%. The results showed that Age Company showed insignificant value of 0.744> 0.05 (p value> 0.05), with no significant effect, Return Market (market conditions) indicates partially insignificant value of 0.196> 0.05 (p value> 0.05), and company size also showed significant results for 0.123> 0.05 (p value> 0.05),